The Role of Arabic Situational Teaching for Spoken Arabic Proficiency: Case Study of Elementary School Students in Malang - Ritonga, Apri Wardana; Abdullah, Muhammad Yahya; Handika Ahmad Nur Prasetyo (Indonesian Journal of Arabic Education and Learning, 2025)
The problem of speaking Arabic (ESA) is often an important issue in teaching Arabic to students. The situational language teaching (SLT) approach is seen as being able to be a solution to this problem. This study aims to analyze the approach of SLT to improve the ESA skills of primary school students. This study uses a qualitative approach with a case study method at Daarul Ukhuwwah Qur’an Basic School, Malang. The research sample is 45 students and 3 teachers. Data was collected through observation, interview, and document study. Then analyzed using the theory of Miles and Huberman. The results of the study show that the SLT approach makes students involved in communicative situations that are similar to their daily lives, but in a more formal context and in accordance with ESA. Teachers can arrange situations that demand the use of formal Arabic, such as class discussions, presentations, or role-plays involving situations in school or other formal environments. The SLT approach is also a solution for improving the Arabic language skills of primary school students starting with istima’, kalam, qira’ah, and kitabah in the context of real situations in everyday life.